Improving Students' Reading Ability Using E-Book Media in Class III UPTD SD 35 Barru - Tarman, Tarman; Rahmadani, Dwi Suci; Adinda, Adinda; Nanda, Nurul Isra (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to address the issues outlined earlier, specifically in improving students’ reading skills through the use of e-book media in Grade III at UPTD SDN 35 Barru. Based on the results of the initial tests, it was found that students’ comprehension of reading material was generally very low, as reflected in the low percentage scores across various aspects. Therefore, concrete actions are necessary to enhance students’ reading skills so that they can achieve better academic performance. The use of e-book media is expected to help students achieve more optimal learning outcomes. This improvement is evident from the positive changes in learning attitudes and the increased reading skill scores of students in Cycle I and Cycle II. The contribution of e-book media in improving students’ reading skills in the Indonesian language subject has proven to be significant. In Cycle I, the average learning achievement rate reached 73.3%, and it increased to 88.5% in Cycle II.